An Analysis of the Themes in Qalandar Atar’s Ghazals - رشيد, جهاد شكرى (Sulaimani Journal for Humanities, 2020)
The theme of the Qalandari is one of the mystical themes in Qasid’s poems and reflections, and its widespread use, much like its mystical roots, indicates its importance to Qasid. Qalandari poems constitute a unique genre within Qasid’s poetry, which in turn represent, in a special way, the intellectual foundations and mystical orientation for conveying Sufi thought. A study of the Qalandari themes in Al-Attar’s love poems may indicate the intellectual trajectory of Qasid’s mystical poetry, which incorporates the critical themes of mystical poetry, since one of the most important characteristics of mystical poetry is the use of mystical themes. In this article, the researcher attempts to demonstrate the extent of the characteristics of the Qalandari path from Al-Attar’s perspective and then to clarify the significance of its influence in Qasid’s love poems.
Keywords: Qasid; Atar; Dervish; Qlender core